Governing HPV-related carcinoma using vaccines: Bottlenecks and breakthroughs - Bhattacharjee, Rahul; Kumar, Lamha; Dhasmana, Archna; Mitra, Tamoghni; Dey, Abhijit; Malik, Sumira; Kim, Bonglee; Gundamaraju, Rohit (Frontiers in Oncology, 2022)
Human papillomavirus (HPV) contributes to sexually transmitted infection, which is primarily associated with pre-cancerous and cancerous lesions in both men and women and is among the neglected cancerous infections in the world. At global level, two-, four-, and nine-valent pure L1 protein encompassed vaccines in targeting high-risk HPV strains using recombinant DNA technology are available. Therapeutic vaccines are produced by early and late oncoproteins that impart superior cell immunity to preventive vaccines that are under investigation. In the current review, we have not only discussed the clinical significance and importance of both preventive and therapeutic vaccines but also highlighted their dosage and mode of administration. This review is novel in its way and will pave the way for researchers to address the challenges posed by HPV-based vaccines at the present time.